BASIS OF FORMATION OF PEREYONYMS IN LINGUISTICS - Sidiqova N.N. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In the article, the terms given to the types of transport, their role in enriching lexicology and from them in literature methods of use are discussed.